Promoting Students’ Collective Socio-scientific Activism: Teachers’ Perspectives - Reis, Pedro (2014)
This chapter describes analyses for the ‘We Act’ project, which is intended to foster development, implementation and study of materials and meth- odologies aimed at supporting teachers and students in taking informed and nego- tiated actions to address social and environmental issues associated with the fields of science and technology. This project combines development, action and research components and crosses three different areas: (1) the promotion of an active inquiry-based learning regarding real-life controversies associated with science and technology; (2) the stimulation of students’ participation in collective demo- cratic problem-solving action; and (3) the support of the first two areas with art initiatives and uses of Web 2.0 tools. Through a qualitative approach, this chapter discusses teachers’ motivations for participating in such a project and also difficul- ties they identify in their students’ enrolment in activism on social and environ- mental issues associated with science and technology. The data obtained through an online questionnaire and semi-structured interviews involving all the teachers in the project were submitted to content analysis. Teachers’ participation in the project is mainly motivated by a strong willingness to find ways to: (a) change what they consider to be students’ apathy concerning school science activities; and (b) empower them for democratic problem-solving action regarding social and environmental problems affecting society. Through the involvement in the project and actions implemented by their students, they began: (a) considering research- informed action as a major aspect of scientific literacy; and (b) recognizing students as important agents of change (capable of implementing, with success, impacting actions on their families and groups of friends) and, consequently, as ‘citizens’ (as opposed to ‘future citizens’). However, they face important obstacles in the implementation of these collective actions; namely, time restrictions imposed by overcrowded curricula and difficulties in finding the ‘proper’ controversial topics capable of overcoming student apathy.